2004
DOI: 10.1007/s00401-004-0937-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 8-oxoguanine DNA glycosylase (OGG1) in Parkinson?s disease and related neurodegenerative disorders

Abstract: Oxidative stress including DNA oxidation is implicated in Parkinson's disease (PD). We postulated that DNA repair enzymes such as 8-oxoguanosine DNA glycosylase (OGG1) are involved in the PD process. We performed immunohistochemical and biochemical studies on brains of patients with PD and those of patients with progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) as disease controls, and control subjects. We found higher expression levels of mitochondrial isoforms of OGG1 enzymes in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 125 publications
(82 citation statements)
references
References 31 publications
5
77
0
Order By: Relevance
“…9 Furthermore, we recently also found a highly increased expression of a mitochondrial form of OGG1 (hOGG1-2a) in dopamine neurons in the SN of PD patient brain, thus supporting our hypothesis that 8-oxoG accumulated in mitochondrial DNA is somehow toxic to dopamine neurons. 30 The present study strongly suggests that the increased expression of MTH1 in the dopamine neurons of PD patients may attenuate their progressive degeneration, and an experimental demonstration of this hypothesis would shed light on the development of new strategies for the therapeutic treatment of PD.…”
Section: Discussionmentioning
confidence: 57%
“…9 Furthermore, we recently also found a highly increased expression of a mitochondrial form of OGG1 (hOGG1-2a) in dopamine neurons in the SN of PD patient brain, thus supporting our hypothesis that 8-oxoG accumulated in mitochondrial DNA is somehow toxic to dopamine neurons. 30 The present study strongly suggests that the increased expression of MTH1 in the dopamine neurons of PD patients may attenuate their progressive degeneration, and an experimental demonstration of this hypothesis would shed light on the development of new strategies for the therapeutic treatment of PD.…”
Section: Discussionmentioning
confidence: 57%
“…We and others have shown that an accumulation of 8-oxoG in mtDNA with increased expression of MTH1, OGG1 and MUTYH in the brains of PD and AD patients (Shimura-Miura et al, 1999;Iida et al, 2002;Fukae et al, 2005;Arai et al, 2006), and involvement of the calpain-cathepsin pathway, are implicated in various neurodegenerative disorders including PD and AD (Saito et al, 1993;Mouatt-Prigent et al, 1996). We have also demonstrated that 8-oxoG accumulation in mtDNA of striatal dopaminergic nerve terminals triggers their retrograde degeneration in a mouse model of PD (Yamaguchi et al, 2006).…”
Section: Mutyh-initiated Cell Death and Its Implication In Carcinogenmentioning
confidence: 58%
“…Expression levels of MTH1, OGG1, and MUTYH are also significantly altered in the brains of such patients (16,(19)(20)(21)(22), suggesting that their altered expression along with accumulation of 8-oxoG in brain cause neurodegeneration; however, how 8-oxoG and these enzymes are associated with the neurodegenerative process is poorly understood.…”
Section: Introductionmentioning
confidence: 99%